Fibrin-targeted recombinant hirudin inhibits fibrin deposition on experimental clots more efficiently than recombinant hirudin. - Bode, Christoph; Hudelmayer, Michael; Mehwald, Petra Susanne; Bauer, Simone; Freitag, Mathias; Hodenberg, Eberhard von; Newell, John B.; Kübler, Wolfgang; Haber, Edgar; Runge, Marshall Stevens (Circulation, 1994)
BACKGROUND - Although the indirect thrombin inhibitor heparin and the more potent direct inhibitor hirudin are useful in preventing thrombosis, a substantial opportunity remains for improving the thrombus selectivity of thrombin inhibitors. - METHODS AND RESULTS - To explore the effect of targeting an antithrombin to the surface of a clot, we covalently linked recombinant hirudin to the Fab' (or IgG) of a monoclonal antibody (59D8) that selectively binds to an epitope on fibrin that becomes exposed only after thrombin cleaves fibrinopeptide B. Antibody-coupled hirudin bound to an immobilized peptide of the fibrin beta-chain amino-terminal sequence and inhibited the peptidolytic activity of thrombin more efficiently than free hirudin. Thrombin inhibition dependent on binding to immobilized fibrin monomer was enhanced 1100-fold (P < .0001). Hirudin-59D8 Fab' was 10 times more effective than hirudin in inhibiting fibrin deposition on experimental clot surfaces in fibrinogen solution (P < .0001) and human plasma (P < .0001). The more effective inhibition of thrombin by the conjugate was supported by significantly diminished concentrations of fibrinopeptide A in the plasma supernatant of the clot (P = .0001). Inhibition of clotting by an uncoupled mixture of hirudin and 59D8 Fab' was indistinguishable from that by hirudin alone, indicating that the conjugate's greater inhibitory activity was due to the covalent linkage between antibody and hirudin. - CONCLUSIONS - Fibrin-targeted hirudin (in comparison with unmodified hirudin) significantly reduces fibrin deposition on the surface of experimental clots.